Pengaruh Thin Capitalization, Sales Growth, Capital Intensity terhadap Tax Avoidance dengan kepemilikan Institusional sebagai Moderasi - Norsiah, Siti; Pratiwi, Adhitya Putri (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to examine the effect of Thin Capitalization, Sales Growth, and Capital Intensity on Tax Avoidance, with Institutional Ownership as a moderating variable in coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The background of this study is based on the importance of tax management as a company efficiency strategy, while maintaining compliance with tax regulations. The coal industry was chosen because of its capital-intensive characteristics, fluctuating sales growth rates, and the tendency of companies to engage in aggressive tax planning. The research method uses a quantitative approach with a purposive sampling technique, resulting in 50 company samples during the observation period. Data were analyzed using multiple linear regression with the help of E-Views 13 software to test the direct relationship between variables, and Moderated Regression Analysis (MRA) to test the role of Institutional Ownership as a moderating variable. The results show that Thin Capitalization has no significant effect on Tax Avoidance, which indicates that high debt ratios are not always utilized by companies to reduce tax burdens. Capital Intensity also had no significant effect on Tax Avoidance, indicating that the size of fixed asset investments does not directly influence tax avoidance practices. Conversely, Sales Growth had a significant positive effect on Tax Avoidance, indicating that high sales growth tends to encourage companies to optimize tax-saving strategies. Furthermore, the results of the moderation test revealed that Institutional Ownership did not moderate the relationship between Thin Capitalization, Sales Growth, or Capital Intensity on Tax Avoidance. This finding suggests that the supervisory role of institutional shareholders is ineffective in limiting or influencing tax avoidance strategies in coal companies. This research provides implications for regulators and investors to consider non-financial factors and governance mechanisms in efforts to control tax avoidance practices in strategic sectors like coal.